Predisposing factors for suicide risk in adults: a systematic review - Nicho-Almonacid, Tracy L. (2023)
The present study was carried out with the purpose of identifying the predisposing factors of suicide risk in the adult population. For this reason, a systematization of the empirical evidence accumulated in the last 10 years was carried out, based on the search for scientific articles indexed in databases such as Scopus, Web of Science, PubMed, APA PsycNet and SpringerLink. A sample of 44 documents that met the following inclusion criteria was obtained: empirical research on psychosocial variables and sociodemographic factors related to suicide risk in the adult population, published between 2012 and 2022, available in full text, in Spanish and English. In the same way, the documentary analysis technique was applied and an information matrix was used as an instrument in which the most relevant data of the studies examined were recorded. As results, it was found that the psychosocial variables most associated with suicide risk are depression, anxiety, alcohol consumption and social support, while sociodemographic factors are gender, living alone, marital status, and a history of physical and mental illness.